A vertical empire history of the British rocketry programme - Hill, C. N. (Imperial College Press, 2012)
Provides a description of the British rocketry and space programme from the 1950s to 1970s, detailing the Medium Range Ballistic Missile Blue Streak and its conversion to a satellite launcher as part of the European Launcher Development Organisation (ELDO).